Diseño de un Sistema de Gestión del Talento Humano del Hotel Mansión Santa Isabella de la Ciudad de Riobamba Provincia de Chimborazo. - Yanez Quintana, Veronica Mariana (2012)
The present work is for designing a Human Talent Management System at Santa Isabella Mansion Hotel in Riobamba, this work will contribute in its organizational development. For this, the tourist and hotelier management, the hotelier industry, the human talent management system, and the human talent management models have been science-based, followed by the hotel human talent actual information. This important information helped us to complete the development of the research for making a management model based on theories about Idalberto Chiavenato, since it is according to the needs this hotel requires. By means of the processing and analysis of surveys we have obtained results that allow us to implement a proposal of a model for Human Resource Management because it doesn’t exist and it has also been seen that not all the staff have enough knowledge and training according to the functions performed, there are also frequent staff changes. All these aspects influence in a negative way in the type of service offered to external and internal customers.